Identification of the Characteristics of the Industrial System of the Multilevel Urban Agglomeration in the Pearl River Delta - Song, Yao; Yu, Yanxu; Mao, Jiansu (Journal of Environmental Accounting and Management, 2026)
Hierarchical study of the industrial systems (ISs) of urban agglomerations, as compound systems under the interaction of multiple cities, is of great significance to the planning and management of a specific region. In the Pearl River Delta, one of the most vigorous economic zones in China, the developments of its nine component cities are unbalanced. Taking this area as a research object can not only promote its coordinated and sustainable development but can also predict and guide the industrial development of other regions. This study divides the Pearl River Delta into three levels from inside to outside as follows: Shenzhen, the urban belt composed of Guangzhou, Shenzhen and Dongguan, and the urban agglomeration composed of nine cities. According to the material flow process from resources to products, a framework of the relations between each component of an IS and the external environment as well as an evaluation index system are established. On this basis, taking China as a basic standard, the industrial characteristics of the three levels are quantitatively analyzed and compared. The results show that the concentration in the product processing and manufacture phase (PM), especially in the the manufacturing sector of computers, communication and other electronic equipment (CEM), is more significant in the Pearl River Delta compared with China and that the dominance of CEM becomes increasingly obvious with the convergence to the core city. This area also has characteristics of higher profits, lower energy consumption and lower pollutant discharges, which are 2.17%, 74.55% and 74.52% better than those of China, respectively. Shenzhen, whose discharges of smoke and dust and waste solids are as low as 0.43 ton/billion CNY and 0.51 ton/billion CNY, respectively, plays a leading role in energy saving and discharge reduction in the urban agglomeration. Huizhou, Zhaoqing and Jiangmen are key cities to increase the energy efficiency of the IS in the Pearl River Delta, whereas Dongguan is the key city to enhance the positive driving effect of the central city belt to marginal cities.